IMPLEMENTASI BUDIDAYA MICROGREEN DALAM EXPEDITIONARY LEARNING BAGI SISWA SEKOLAH ALAM DI KABUPATEN KARAWANG - Laksono, Rommy Andhika; Srisudarso, Mansyur; Bayfurqon, Fawzy Muhammad; Pertiwi, Anggun (STKIP Persada Khatulistiwa Sintang, 2024)
ABSTRACTThe average vegetable consumption of the Indonesian population is 70 grams/person/day. When compared with the recommended adequacy according to balanced nutrition guidelines, the level of vegetable consumption is still relatively low. As many as 97.1% of the population does not consume enough vegetables. Teenagers are the highest age group who consume less vegetables. The aim of this service activity is to implement the Expeditionary Learning model of teacher and student learning in microgreen cultivation as an effort to increase the interest of natural school students/teenagers in consuming vegetables independently. Abdimas is carried out at the Inaratul Islam natural school located in Kec. Purwasari, Kab. Karawang, West Java in May-October 2024. The service method is carried out using training, demonstration and mentoring methods for natural school teachers and students. The results achieved by Microgreen Cultivation in Expeditionary Learning in students were able to increase 80% of the knowledge, attitudes and skills of the participants. This PKM activity is also able to stimulate students to be more active, independent, and care about the environment and body health.Keywords: Microgreens, Expeditionary Learning, Nature School ABSTRAKRata-rata konsumsi sayur penduduk Indonesia yaitu 70 gram/orang/hari. Bila dibandingkan dengan kecukupan yang dianjurkan menurut pedoman gizi seimbang, tingkat konsumsi sayur tersebut masih tergolong rendah. Sebanyak 97,1 % penduduk kurang mengonsumsi sayur. Kaum remaja adalah kelompok umur tertinggi yang kurang mengonsumsi sayur. Tujuan dari kegiatan pengabdian ini adalah mengimplemantasikan model Expeditionary Learning pembelajaran guru dan siswa dalam budidaya microgreen sebagai upaya peningkatan minat siswa/remaja sekolah alam dalam mengkonsumsi sayur secara mandiri. Abdimas dilaksanakan di sekolah alam Inaratul Islam yang terletak di Kec. Purwasari, Kab. Karawang, Jawa Barat pada bulan Mei-Oktober 2024. Metode pengabdian dilakukan menggunakan metode pelatihan, demontrasi, dan pendampingan terhadap guru dan siswa sekolah alam. Hasil yang dicapai Budidaya Microgreen dalam Expeditionary Learning pada siswa mampu meningkatkan 80% pengetahuan, sikap dan keterampilan pesertanya. Kegiatan PKM ini juga mampu merangsang siswa untuk lebih aktif, mandiri, dan peduli terhadap lingkungan dan Kesehatan tubuh.Kata Kunci: Microgreen, Expeditionary Learning, Sekolah Alam